Assessment of Initial Serum Vancomycin Trough Concentrations and Their Association with Initial Empirical Weight‐Based Vancomycin Dosing and Development of Nephrotoxicity in Children: A Multicenter Retrospective Study. Issue 3 (10th March 2015) - Matson, Kelly L.; Shaffer, Christopher L.; Beck, Gary L.; Simonsen, Kari A.
Abstract : Study Objectives: To determine whether a relationship exists between initial serum vancomycin trough concentrations and initial empirical vancomycin dose, patient weight, and patient age, and to determine the risks for vancomycin‐associated nephrotoxicity in pediatric patients stratified by hospital setting. Design: Stepwise linear and multinomial logistic regression analysis of retrospectively collected data. Setting: Two geographically distinct children's tertiary care medical centers. Patients: A total of 316 pediatric patients without preexisting renal dysfunction who were managed outside of the neonatal intensive care unit and were treated with at least 3 doses of vancomycin for gram‐positive bacterial infections and had at least one serum vancomycin trough concentration between January 1, 2008, and July 31, 2010. Measurements and Main Results: Elevated vancomycin trough concentrations had no statistically significant relationship with initial empirical vancomycin dosing across all hospital settings. Serum vancomycin trough concentrations (lower than 15 mg/L or 15–20 mg/L) were not associated with increased risk of nephrotoxicity. Concomitant nephrotoxic agents, however, including loop diuretics, vasopressors, angiotensin‐converting enzyme (ACE) inhibitors, and nonsteroidal antiinflammatory drugs (NSAIDs) were significantly associated with the development of nephrotoxicity in medical‐surgical and intensive care patients. Based on this analysis, use of loop diuretics and vasopressors increased the odds of developing nephrotoxicity (odds ratio [OR] 42.8 [p=0.001] and 18.4 [p=0.02], respectively). Use of NSAIDS and ACE inhibitors also increased the odds of developing nephrotoxicity (OR 18.6 [p=0.02] and 4.7 [p=0.03], respectively). Conclusion: No significant associations were found between initial empirical weight‐based vancomycin dosing or elevated serum trough concentrations and development of nephrotoxicity in children; rather, nephrotoxicity was associated with combination therapy with vancomycin and other potentially nephrotoxic agents.